Islamic Entrepreneurship among Nonimmigrant Muslims in Small Venture Creation - Aaron A. Vargas-Zeledon (Universitas Muhammadiyah Yogyakarta, 2023)
This study examines the relationship between Islamic entrepreneurship and nonimmigrant Muslims in small venture creation. It seeks to establish whether the motivation of nonimmigrants increases the profile of the Islamic form of entrepreneurship derived from factors affecting nonimmigrant Muslims. The logical paradigm of a self-administered questionnaire in the city of Gwangju was used to generate descriptive data to evaluate the view and attitudes of nonimmigrant Muslims in terms of Islamic forms of entrepreneurship. The study finds that nonimmigrant Muslims sense themselves to be devoted Muslims related to entrepreneurship as a religious and economic activity intended to create income to meet their appreciation and to contribute to the well-being of the Muslim community. Also, the findings similarly invalidate the widespread usual statements that Islam is essentially an anti-entrepreneurial religion derived from the religiously-based of nonimmigrant Muslims. There is a negative and positive balance related to factors affecting the influence of Islamic entrepreneurship among nonimmigrant Muslims. Therefore, this study makes important contributions in terms of theory building within the context of nonimmigrant Muslims.